A defesa nacional e os programas estratégicos de defesa no PPA 2016 - 2019 - Luís Felipe Giesteira; Patrícia de Oliveira Matos; Thiago Borne Ferreira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– This paper assesses the Brazilian National Defense Policy considering the objectives established by the National Defense Policy (PDN), the National Defense Strategy (END) and the National Defense White Paper (LBDN). It seeks to clarify whether the goals listed in such documents have been achieved, especially with regard to technological autonomy and the strengthening of the Industrial Defense Base (IDB) in Brazil. To this end, we analyzed the sector's budget allocation as provided by the 2016-2019 Pluriannual Plan (PPA), relating actions, objectives and targets to the Ministry of Defense (MD) Strategic Programs. It is concluded that, despite the adverse economic situation registered in the country over the period, there was a growth in investments in projects with relatively high technological content. However, the research also showed that the same trend did not occur in areas equally important for National Defense, such as the nuclear and space sectors.
Keywords: H56; H61; O21; O22; 330; National Defense Policy; Pluriannual Plan; defense budget; technological innovation; strategy